Africa, a Young and Heterogeneous Continent Facing up to Aging: Issues of Social Protection for the Elderly - (:unkn) unknown (My University, 2015)
The African continent is characterized by its demographic and economic heterogeneity, something that is reflected in the variety of social protection systems for older people. There is uneven provision for health and age-related risks, with social protection based on contributory and/or non-contributory schemes. In the context of a progressive expansion of their coverage, the expected rapid growth of the aged population needs to be integrated into the development of social policy.
Keywords: African Research